Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1093/hmg/ddm153
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution of primate ESX1 , an X-linked placenta- and testis-expressed homeobox gene

Abstract: Homeobox genes encode transcription factors that play important roles in various developmental processes and are usually evolutionarily conserved. Here we report a case of rapid evolution of a homeobox gene in humans and non-human primates. ESX1 is an X-linked homeobox gene primarily expressed in the placenta and testis, with physiological functions in placenta/fetus development and spermatogenesis. ESX1 is paternally imprinted in mice, but is not imprinted in humans. We provide evidence for a significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 46 publications
0
15
1
Order By: Relevance
“…The Tex19 gene was first identified as a unique gene and with a male germ cell-specific expression [11]. Subsequently, we showed that Tex19 is duplicated in the mouse and rat, giving rise to Tex19.1 and Tex19.2 paralogs [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tex19 gene was first identified as a unique gene and with a male germ cell-specific expression [11]. Subsequently, we showed that Tex19 is duplicated in the mouse and rat, giving rise to Tex19.1 and Tex19.2 paralogs [2].…”
Section: Discussionmentioning
confidence: 99%
“…Many genes have been ascribed a specific expression either in somatic or germ cells in the gonads and in placental cell populations. This is the case for Esx1 [11] and a cluster of genes representing the Rhox homeobox gene family, which includes Rhox5 (or Pem) [12], Rhox6 (or Psx1) [13] and Rhox9 (also known as Psx2 or Gpbox) [14]. Three of these genes have been successfully ablated in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Another intriguing aspect of Esx1 is that, like Rhox5, it has undergone rapid evolution in mammals (Wang & Zhang 2007). Evidence suggests that positive selection for rapid changes has primarily occurred in the C-terminal region, which is the region that regulates cyclin degradation and cell division.…”
Section: Esx1/esx1mentioning
confidence: 99%
“…X-linked genes are believed to evolve more rapidly than their autosomal orthologues due to their hemizygosity in males [17,18]. The mammalian sex chromosomes emerged from an ancestral pair of autosomes [19] and have received specific additions and deletions in each lineage.…”
Section: Introductionmentioning
confidence: 99%